The Role of PAX9 and MSX1 Variants in Non-Syndromic Tooth Agenesis - Finna; Ameta Primasari; Sry Suryani Widjaja; Thantrira Porntaveetus; Ervina Sofyanti (Dentika: Dental Journal, 2025)
Non-syndromic tooth agenesis (NSTA) is the congenital absence of teeth without systemic involvement. Genetic polymorphisms in PAX9 and MSX1 are implicated in tooth development, but results vary across populations. Therefore, this study aims to explore the role of PAX9 c.-1031G>A and MSX1 671 T>C polymorphisms with NSTA in individuals from Medan. A total of 13 NSTA patients and 26 control were genotyped using PCR-restriction fragment length polymorphism (PCR-RFLP). The results showed that the AA genotype of PAX9 was absent in NSTA cases but found in 26.92% of controls. The GG genotype was reported to be more common in 38.46% of cases, while the G allele was prevalent in 69.23%. These trends suggested a potential association, but it was not statistically significant. In this study, all patients carried the TT genotype for MSX1. These results show a possible role of PAX9 polymorphisms in NSTA susceptibility and support the need for further studies in larger populations.   Keywords: Non-Syndromic, Tooth Agenesis, PAX9, MSX1